2014
DOI: 10.3354/meps10959
|View full text |Cite
|
Sign up to set email alerts
|

Jellyfish biochemical composition: importance of standardised sample processing

Abstract: Jellyfish play a key role in many pelagic ecosystems, especially in areas of extensive bloom events. In order to understand their role in pelagic food webs and in biogeochemical cycling, the energy stored and the trophic level occupied by jellyfish need to be quantified. To date, the common protocols applied for quantifying jellyfish biomass and analyzing its biochemical composition have been the same as for crustacean zooplankton, despite the difference in the body composition of the 2 groups. With the goal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 69 publications
4
30
1
Order By: Relevance
“…Ash content is a measure of the amount of inorganic minerals present in the sample and is generally between 3.0 and 7.8% of the dry biomass in different rotifer species (Watanabe, Kitajima, & Fujita, 1983;Jeeja, Joseph, & Malej, 2011); however, in our samples of P. similis, the ash contents were between 23.8 and 46.85% DB, which contrast with the values reported for other species of rotifers, but are very similar to those reported for gelatinous species (>50% DB) (Clarke, Holms, & Gore, 1992;Kiørboe, 2013), probably because of the close relationship of the family Proalidae with other gelatinous organism or jelly plankton as stated by Dumont (2007). Hirst andLucas (1998), andKogovsek, Tinta, Klum, andMalej (2014), mentioned that it is common that gelatinous species show an increase in dry biomass and ash content with increasing salinity. This may have important nutritional implications if P. similis is used for larval feeding, since it has been reported that gelatinous species have low nutritional quality (Doyle, Houghton, McDevitt, Davenport, & Hays, 2007); however, this aspect requires further investigation in the different strains of P. similis from different geographical regions.…”
Section: Discussioncontrasting
confidence: 54%
“…Ash content is a measure of the amount of inorganic minerals present in the sample and is generally between 3.0 and 7.8% of the dry biomass in different rotifer species (Watanabe, Kitajima, & Fujita, 1983;Jeeja, Joseph, & Malej, 2011); however, in our samples of P. similis, the ash contents were between 23.8 and 46.85% DB, which contrast with the values reported for other species of rotifers, but are very similar to those reported for gelatinous species (>50% DB) (Clarke, Holms, & Gore, 1992;Kiørboe, 2013), probably because of the close relationship of the family Proalidae with other gelatinous organism or jelly plankton as stated by Dumont (2007). Hirst andLucas (1998), andKogovsek, Tinta, Klum, andMalej (2014), mentioned that it is common that gelatinous species show an increase in dry biomass and ash content with increasing salinity. This may have important nutritional implications if P. similis is used for larval feeding, since it has been reported that gelatinous species have low nutritional quality (Doyle, Houghton, McDevitt, Davenport, & Hays, 2007); however, this aspect requires further investigation in the different strains of P. similis from different geographical regions.…”
Section: Discussioncontrasting
confidence: 54%
“…The time framework of dietary composition provided by stomach content analysis has been extended by combining or replacing this approach with stable isotope analysis (SIA;Brodeur et al 2008, Shoji et al 2009, Nagata et al 2015. Although sample processing protocols have been refined (Fleming et al 2011, D'Ambra et al 2014, Kogovšek et al 2014, the interpretation of stable isotope values in jellyfish is challenged by the unusual diet-tissue discrimination factors (DTDFs) from scyphomedusae to their prey. The DTDFs of a large variety of invertebrates and fish fall within the range 1.4 ± 1 ‰ (mean ± SD) for carbon (C) and 3 ± 1 ‰ for nitrogen (N) (McCutchan et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…(Kogovšek et al . ) compared several methods used for the study of jellyfish biochemical composition and established that during drying in the oven at 60C, the content of C, N and the total content of amino acids in the jellyfish tissue decreases 10 times as compared with cool dehumidification.…”
Section: Introductionmentioning
confidence: 99%